(untitled) (Indian Journal of Animal Production and Management, 2018)
The present experiment was carried out to compare the effect of microclimate on rectal temperature (RT) and body surface temperature (BST) of black and white indigenous breeds of goat. Diurnal variation of ambient temperature (AT) and relative humidity (RH) were recorded at hourly intervals inside goat pen and temperature humidity index (THI) was calculated. The RT and BST (fore head, back, rump, flank, hind cannon, udder and chest) were monitored twice a day (morning and afternoon) at fortnightly intervals in twelve female goats (6 each of black and white body coat coloured breed). The mean AT, RH and THI of pens were 24.86±0.98 ºC (ranged from 18.3 to 33.3 ºC), 51.06±2.51% (ranged from 30.4 to 70.9%) and 71.14±1.00 (ranged from 63.9 to 78.8), respectively. The RT and BST at fore head, back, rump, flank, hind cannon and chest regions increased significantly from morning to afternoon (P<0.001). Coat colour did not affect RT, but significantly affected BST at rump (P=0.048), hind cannon (P<0.001) and chest (P=0.038). However, BST at fore head, back, flank and udder was not influenced by coat colour. There was significant interaction effect of time of day and coat colour on BST at back region (P=0.039), where BST increased markedly in white coloured goats than their black counterparts (11.24 vs. 8.19%). The results indicated that the goats experienced mild to moderate heat stress. The coat colour influenced body surface temperature of goats in certain body regions; however, heat tolerance ability of black and white coloured goat breeds did not differ.